The Hudson River Estuary - Levinton, Jeffrey S.; Waldman, John R. (Cambridge University Press, 2006)
The Hudson River Estuary is a comprehensive look at the physical, chemical, biological and environmental management issues that are important to our understanding of the Hudson River. Chapters cover the entire range of fields necessary to understanding the workings of the Hudson River estuary; the physics, bedrock geological setting and sedimentological processes of the estuary; ecosystem-level processes and biological interactions; and environmental issues such as fisheries, toxic substances, and the effect of nutrient input from densely populated areas. This 2006 book places special emphasis on important issues specific to the Hudson, such as the effect of power plants and high concentrations of PCBs. The chapters are written by specialists at a level that is accessible to students, teachers and the interested layperson. The Hudson River Estuary is a fascinating scientific biography of a major estuary, with relevance to the study of any similar natural system in the world.